A study on parallel importers and authorized agents in Singapore car industry. - Chua, Ming Jie. (2010)
In Singapore’s automobile industry, the authorized agents are the dominant players and parallel importers take on the secondary role. In a news article from The Straits Times in October 2007, it was reported that one in every five car sold was a parallel import. And while the market share of the parallel importers has doubled in five years, complaints to the Consumers Association of Singapore (CASE) have also risen. With such complaints, these could have affected the image and reputation of the parallel importers. Thus, our study aimed to find out car owners’ perceptions on purchasing cars from parallel importers and authorized agents and the difference in demographics of car owners who purchased cars from parallel importers or authorized agents. The study also investigated how car owners’ perceptions affect their willingness to purchase cars from authorized agents. Perception is one of the factors that have influence on buyer’s purchase decision in most products and services. Through the findings of the survey from this research, we found out that majority of the car owners in Singapore purchased their cars from the authorized agents and perceived them as providing better after-sales service and more assurance. This group of car owners who purchased cars from the authorized agents was generally found in the older age group, had higher education level (degree and above) and with monthly household income of more than S$5500.